Legal Protection for Notary Public in Performing Their Duties As A General Officer Based on Law of Notary Office in Kendari Region - Danu Giritono (Sultan Agung Notary Law Review, 2020)
This research was conducted using a normative juridical or statutory approach. With the aim of approaching the problem by looking at the prevailing laws and regulations regarding legal protection against notaries for data forgery by clients in the Kendari city area. Forms of legal protection for Notaries in the city area, although in making authentic deeds, they must pay attention to the principles of prudence, thoroughness, and uphold honesty, morality and not forgetting professionalism. Meanwhile, the form of legal protection from the Notary Honorary Council is to carry out supervision and examination for Notaries so that they can continue to walk on the right path in accordance with the Law. When a Notary is summoned in a criminal case, the MKN has the authority to agree to be examined or not to be examined as long as the Notary has acted in accordance with UUJN and/or the relevant laws and regulations in connection with the deed made before him, MKN should not give the Notary's approval to be examined or attend the trial.